Kedudukan Hukum Surat Peringatan (SP) dan Skorsing dalam Proses PHK Buruh/Pekerja - Dede Agus (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Warning letter (SP) is an effort to avoid layoffs (PHK), because warning letter does not decide an employment relationship immediately. Sometimes, an employer ignore warning letter in practice and they give skorsing letter directly. Although the warning letter and skorsing have a different law status. Therefore, this paper is aimed to discuss warning letter and skorsing law status in labour/an employee layoffs process. Warning letter and skorsing were given labour/an employee by employer before layoffs, but warning letter and skorsing have a difference of principle. Warning letter educate labour/an employee to take responsibility and still not yet layoffs process, but skorsing is given labour/an employee by employer in layoffs process. It propose and wait layoffs decision from institutions of industrial relations disputes settlement.